Environmental Ethics in Tarjumān al-Mustafīd: Interpretation of QS. Ar-Rūm 41 in 17th Century Malay Society - Muhammad Syukron Zun-Nurain; Ris'an Rusli; Abdul Kher; Nur Fitriyana; Hafizuddin Bin Sham Shul Bahr (ZAD Al-Mufassirin, 2026)
This study examines the construction of environmental ethics in the interpretation of QS. Ar-Rūm [30]:41 in Tarjumān al-Mustafīd and its relationship to the socio-historical context of seventeenth-century Malay Muslim society. Employing a qualitative library research method, this study analyzes Tarjumān al-Mustafīd as the primary source, supported by classical Qur’anic commentaries, studies on Malay Islamic intellectual history, and contemporary literature on Islamic ecotheology. Anthony Giddens’ structuration theory is utilized to examine the reciprocal relationship between exegetical discourse and the socio-religious structures within which the tafsir was produced, transmitted, and received. The findings demonstrate that the concept of fasād in QS. Ar-Rūm [30]:41 is interpreted not merely as moral and religious corruption but also as social and ecological degradation resulting from human actions. The interpretation reflects the contextualization of Qur’anic teachings within the historical realities of seventeenth-century Malay society, where religious knowledge functioned both as a product of existing social structures and as a medium for shaping ethical consciousness and communal order. This study contributes to the fields of Nusantara Qur’anic exegesis and Islamic ecotheology by revealing how environmental ethics were articulated in an early Malay tafsir through the dynamic interplay of scriptural interpretation, socio-historical context, and religious authority. The findings further offer a historical foundation for contemporary Islamic environmental discourse in Southeast Asia.